Estimating of the vibration levels for truck transport in Iran - Ramezani Boukat, Ali; Navid, Hossein; Musevi Niya, Mir Javad; Ranjbar, Sajjad (Revista Agrogeoambiental, 2021)
A wide-ranging of distribution environments could affect designing packages. The first step in the proper packaging design of agricultural products, particularly fruit, is to conduct a precise simulation of the truck transport. Thus, this research was conducted to analyze the vibration levels for truck transport using multi-sensor-based computing on packaged fruit in Iran (the first), one of the leading agriculture in Middle East Asia. Towards this goal, a wireless sensor network made of three sensor nodes with tri-axial accelerometers was designed to measure the vibration levels for truck transport at three package locations equipped with leaf-spring suspension in local and highway roads. To measure the vibration data a power spectral density function (PSD) levels were applied. Compared to the International Standards (ASTM 4728: West Conshohocken, USA, ISTA: Chicago, USA), the PSD levels of the truck in both roads types were higher in 1 to 35 Hz, and lower in 35 to 200 Hz. In particular, the differences in directional vibration levels were more pronounced in the low-frequency range of 10 Hz in both road types. The highest amount of truck bed acceleration occurred in the packages located at the rear end of the trucks. And, the peak PSD values were obtained as equal to 0.178 G2/Hz (rear-up), 0.136 G2/Hz (rear-down), and 0.096 G2/Hz (front-up) locations, respectively. Meanwhile, the road quality had affected the vibration levels in such a way that the peak PSD value obtained on highways was lower than that of the ones of the local roads. According to the results, the amount of acceleration on the heavy truck beds on the country’s roads can be considered 0.654 G. In sum, the current results can be used to simulate the truck transport conditions by programmable vibration simulators to reproduce the vibration conditions for package testing in Iran roads. And, the findings are of high interest to improve packaging design, reduce fruit damage, maintain shelf life, smart transportation, and related industries.